Identification and Characterization of a Novel Basic Helix-Loop-Helix Transcription Factor of Phospholipid Synthesis Regulation in Aspergillus niger - Dong, Hongzhi; Yu, Dou; Wang, Bin; Pan, Li (Frontiers in Microbiology, 2020)
The synthesis of phospholipids relies on a sort of genes, whose promoter regions contain inositol-sensitive upstream activation sequence (UASINO) and are regulated by the basic helix-loop-helix (bHLH)-type ino2/ino4 transcription factor (TF) pair. Ten putative bHLH TFs have been found through whole genome sequencing of Aspergillus niger, but none of these TFs have been characterized. In this study, we identified and characterized the bHLH-type TF ino2(An02g04350) in A. niger. Electrophoretic mobility shift assay (EMSA) and yeast two-hybrid assay demonstrated that ino2 functions as a homodimer in UASINO genes (e.g., ino1 and cho1) and binds to opi1(An1g02370) in vitro. Real-time quantitative PCR of ino1 and quantification of total phospholipid indicated that the ino2 disruptant downregulated the transcription of ino1 and the amount of total cellular phosphatidylinositol. In addition, phenotype analyses showed that a loss of ino2 led to resistance to cell wall interference and DNA damage. Comparative transcriptome analyses showed that more than 1000 genes and GO terms associated with UASINO, endoplasmic reticulum–associated protein degradation, phosphatidylinositol synthesis, chitin synthesis, and fatty acid synthesis were differentially expressed in Δino2 compared to the wild type (WT). Taken together, these observations indicate that the bHLH TF ino2 functions as a homodimer that regulates the synthesis of phosphatidylinositol, fatty acid, and chitin and influences the homeostasis of the endoplasmic reticulum membrane.